#LOLNothingMatters. (March 2018) - Sagers, Chris
Institutions matter in antitrust, at least as much as ideas. Most antitrust arguments, and especially the contretemps currently enjoying some attention in the popular press, imagine that antitrust problems are short- or medium-term matters, and that they can be corrected with local doctrinal steps. I suggest there is a deeper problem, a phenomenon more deeply inherent in the nature of competition itself. The problem will cyclically recur, so long as institutional brakes are unavailable to keep it at bay. Specifically, it seems that competitive markets are difficult to preserve without some prospective, no-fault rule to control concentration for its own sake. At least nominally, American antitrust has such a rule in its basic merger law, Clayton Act § 7, but the rest of it consists of retrospective, fault-based, law-enforcement rules that in their application are by nature somewhat piecemeal. A prospective concentration rule is needed because once markets become concentrated, situations are common in which neither disciplinary new entry nor retrospective conduct remedies can restore competition. The deeper problem inherent in competition policy, which demonstrates the significance of institutions as well as ideas, is that such a rule is also most difficult to enforce. That is so because markets in their ordinary operation are confusing and contradictory to watch, and the hardest interventions for government to defend to a skeptical public are those that are prospective. Finally, however, it so happens that one institutional correction currently on the legislative agenda could conceivably do some good in correcting for this problem—a specific plank in congressional Democrats' "Better Deal" platform.